The RENAPE observational registry: rationale and framework of the rare peritoneal tumors French patient registry. Issue 1 (December 2017) - Villeneuve, L.; Passot, G.; Glehen, O.; Isaac, S.; Bibeau, F.; Rousset, P.; Gilly, F.
Abstract Background Rare peritoneal cancers represent complex clinical situations requiring a specific and multidisciplinary management. Because of their rarity, lack of awareness and knowledge often leads to diagnostic delays and misdiagnosis. And patients are not systematically referred to expert centers as they should be. Clinicians and researchers also face unique challenges with these rare cancers, because it is hard to conduct adequately powered, controlled trials in such small patient population. This is how an observational patient registry constitutes a key instrument for the development of epidemiological and clinical research in the field of these rare cancers. It is the appropriate tool to pool scarce data for epidemiological research and to assess the impact of diagnostic and therapeutic strategies. We aimed to provide the outlines and the framework of the RENAPE observational registry and share our experience in the establishment of a national patient registry. Results The RENAPE observational registry has been launched in 2010 thanks to institutional supports. It concerns only patients with a histological diagnosis confirming a peritoneal surface malignancy. A web secured clinical database has been implemented based on data management procedures according to the principles of international recommendations and regulatory statements. A virtual tumor bank is linked in order to the conduct translational studies. Specialized working groups have been established to continuously upgrade and evolve the common clinical and histological data elements following the last classifications and clinical practices. They contribute also to standardize clinical assessment and homogenize practices. Conclusions The RENAPE Registry may improve awareness and understanding of the rare peritoneal tumors into the incidence, prevalence, recurrence, survival and mortality rates, as well as treatment practices thereby enabling therapeutic intervention to be evaluated and ultimately optimized. Trial registration ClinicalTrials.gov Identifier:NCT02834169